Solve for m: m/5 + 3(m-1)/) = 2(m-3)
2 answers:
<span>m/5 + 3(m - 1) = 2(m - 3)
m + 15(m - 1) = 10(m - 3)
m + 15m - 15 = 10m - 30
6m = -15
m = -15/6</span>
M/5 + 3(m - 1) = 2(m - 3)
Simplify inside the parenthesis.
m/5 + 3m - 3 = 2m - 6
Now, we need to move all variables to the left side of the equal sign, and move all isolated numbers to the other (right) side of the equal sign.
So, we need to add 3 to both sides, and subtract 2m from both sides,
m/5 + 3m - 2m = -6 + 3
Simplify.
m/5 + m = -3
Remember : m/5 is basically 1/5m :)
So, our equation now looks like this :
1/5m + m = -3
Remember, "m" is basically 5/5, because "5" is our common denominator.
So, our equation now looks like this :
1/5m + 5/5m = -3
Simplify.
6/5m = -3
Then, multiply both sides by 5/6 so that m is isolated.
5/6 × 6/5m = -3 × 5/6
Simplify.
m = -5/2 AND -2 1/2 AND -2.5
~Hope I helped!~
You might be interested in
<span>Does this help answer you question?</span>
<span>2x+<span>(2x+2)</span>=234</span>
<span>4x=232</span>
<span>x=58</span>
So, <span>2x=2<span>(58)</span>=116</span>
<span>116+118=234</span>
Answer:
12
Step-by-step explanation:
18 divided my 1.50 is 12
Answer:
21=12+9
Step-by-step explanation:
The right answer may be option 4
Answer
X=28 Degrees
Step-by-step explanation: